17 Conversations on Living and Dying: Facilitating Advance Care Planning for Older People Living with Frailty. A Qualitative Study. (16th March 2021) - Combes, S; Nicholson, C; Gillett, K; Norton, C
Abstract: Introduction: Advance care planning (ACP) is a process that supports people to articulate their future care preferences. This process is a priority for older people living with frailty due to their vulnerability to sudden deterioration, something that has been highlighted during the current pandemic. However, ACP is uncommon for older people living with frailty, hindering choice and person-centred end-of-life care. This study aimed to identify the barriers, facilitators and behaviours required to support cognitively-able, community-dwelling older people living with frailty to engage with ACP. Findings will inform the development an ACP intervention underpinned by behavioural change theory. Methods: Semi-structured interviews with community-dwelling older people living with frailty (Clinical Frailty Score 6 or 7) and family members were audio-recorded, filmed and transcribed verbatim. A thematic analysis framework was developed using a recent systematic review, and expanded to reflect new themes. Results: Ten older people living with frailty and eight family members were interviewed. The older people's median age was 85 and seven were female. Family members were spouses (n = 4) and children (n = 4). The key findings were that: the meaning of ACP could be unclear and at times confusing; many of the older people believed ACP was not relevant to them; relationships and relational autonomy were of greater relevance to older people than autonomous decision-making; older people were more interested in living well now than in planning for the future. Conclusions: Older people living with frailty need to be engaged with ACP in a way that helps them to understand what ACP is and why it is relevant for them. Professionals need to develop their skills in assessing readiness and facilitating ACP conversations with this population at the older person's pace. Reframing ACP to include living well now alongside encouraging family inclusion would also relate better to this populations' lives.